2020
DOI: 10.1158/1055-9965.epi-19-0833
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Pathway Analysis and Effectiveness of Tamoxifen in Danish Breast Cancer Patients

Abstract: Background: Tamoxifen and its metabolites compete with estrogen to occupy the estrogen receptor. The conventional dose of adjuvant tamoxifen overwhelms estrogen in this competition, reducing breast cancer recurrence risk by nearly half. Phase I metabolism generates active tamoxifen metabolites, and phase II metabolism deactivates them. No earlier pharmacogenetic study has comprehensively evaluated the metabolism and transport pathways, and no earlier study has included a large population of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 67 publications
(97 reference statements)
0
8
0
3
Order By: Relevance
“…Findings from this study merit further investigation. They will be used in future work using multiple pathway analysis [ 23 , 57 ] to capture the net effect of these SNPs. Also, future clinical trials are needed to elucidate whether genomic testing could guide dosing of taxane-based therapy to reduce inter-individual variability in effectiveness.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Findings from this study merit further investigation. They will be used in future work using multiple pathway analysis [ 23 , 57 ] to capture the net effect of these SNPs. Also, future clinical trials are needed to elucidate whether genomic testing could guide dosing of taxane-based therapy to reduce inter-individual variability in effectiveness.…”
Section: Discussionmentioning
confidence: 99%
“…Procedures for collection of FFPE tumor blocks, preparation of the tumor tissue, and DNA extraction are described in detail elsewhere [ 23 ]. Based on a comprehensive review of the taxane pharmacogenetic literature and underlying biology, we identified 26 candidate SNPs.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, no result from the example data set has any evidential value on the topic of genetic modification of tamoxifen therapy effectiveness. Results from ALPS analysis of the real-world tamoxifen metabolic pathway data are reported in a separate publication (33).…”
Section: Data Disclaimermentioning
confidence: 99%
“…в 2020 г. [8]. Оно объединило результаты двух исследований: когортного исследования, включавшего 5959 пациенток в пременопаузе с неметастатическим РМЖ, из которых в 938 случаях возникли рецидивы, а также исследования «случай-контроль», включавшего 541 случай рецидива в когорте преимущественно пациенток с РМЖ в постменопаузе.…”
Section: Introductionunclassified